TEACHER’S QUESTIONING STRATEGIES DURING ENGLISH CLASSROOM INTERACTION AT GRADE X STUDENTS OF SMA NEGERI 2 MEDAN - Juwita Rodearni Saragih; Ade Aini Nuran (Universitas Negeri Medan, 2022)
This research was focused to determine the types of teacher’s questioning strategies, analyzed the dominant types of teacher's questioning strategies and found out the teacher’s reasons of giving question to students. This research was conducted on an English teacher and with grade X natural science 2 students at SMA Negeri 2 Medan. Descriptive qualitative research design was used as a research method while in data collection, observation, video recording and interview were used in this research. During two meetings in collecting data, it was found that at the first meeting the teacher often used a simplification strategy with a total of 19 questions or equivalent to 51%. Meanwhile, in the second meeting, the teacher still used the simplification strategy more with a total of 20 questions, equivalent to 56%. For the overall of the teacher’s questioning strategy namely wait time, repetition, paraphrasing, simplification and probing can be identified in this research. The teacher’s reason gave questions to students was to stimulate students' thinking to think critically, improved vocabulary understanding, clarified student speech, attracted students' interest in learning, checked the extent of student understanding and encouraged students to participating in the classroom. With this questioning strategy, it can be seen that students can be more responsive in answering the teacher questions and the atmosphere in the classroom can be more lively created.